DEVELOPMENT OF DYSBIOSIS AND INFLAMMATION IN RATS TREATED WITH ANTI-HELICOBACTER PYROLI THERAPY AND PREVENTION USING ANTIDYSBIOTIC DRUG "QUERTULIDON" - Shuhtina, I. N.; Petrenko, A. A.; Uspensky, O. E.; Gozhenko, A. I.; Shuhtin, V. V.; Bobrik, L. M.; Boris, R. N. (Journal of Education, Health and Sport, 2015)
Shuhtina I. N., Petrenko A. A., Uspensky O. E., Gozhenko A. I., Shuhtin V. V., Bobrik L. M., Boris R. N. Развитие дисбиоза и воспаления в организме крыс, получавших антихеликобактерную терапию и их профилактика антидисбиотическим препаратом «квертулидон» = Development of dysbiosis and inflammation in rats treated with anti-helicobacter pyroli therapy and prevention using antidysbiotic drug "quertulidon". Journal of Education, Health and Sport. 2015;5(11):227-237. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33876 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A227-237 https://pbn.nauka.gov.pl/works/669474 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 10.11.2015. УДК 616.33:342.092 РАЗВИТИЕ ДИСБИОЗА И ВОСПАЛЕНИЯ В ОРГАНИЗМЕ КРЫС, ПОЛУЧАВШИХ АНТИХЕЛИКОБАКТЕРНУЮ ТЕРАПИЮ И ИХ ПРОФИЛАКТИКА АНТИДИСБИОТИЧЕСКИМ ПРЕПАРАТОМ «КВЕРТУЛИДОН» DEVELOPMENT OF DYSBIOSIS AND INFLAMMATION IN RATS TREATED WITH ANTI-HELICOBACTER PYROLI THERAPY AND PREVENTION USING ANTIDYSBIOTIC DRUG "QUERTULIDON" И. Н. Шухтина1, А. А. Петренко2, О. Е. Успенский3, А. И. Гоженко1, В. В. Шухтин1, Л. М. Бобрик4, Р. Н. Борис1 I. N. Shuhtina1, A. A. Petrenko2, O. E. Uspensky3, A. I. Gozhenko1, V. V. Shuhtin1, L. M. Bobrik4, R. N. Boris1 1ГУ «Украинский НИИ медицины транспорта МЗУ» (г. Одесса) 2 ГУ «Институт стоматологии НАМН» (г. Одесса) 3 Харьковский национальный медицинский университет 4Одесский национальный медицинский университет 1Ukrainian Research Institute for Medicine of Transport 2SE«The Institute of Stomatology of the National acfdemie of medical science of Ukraine» 3Kharkiv National Medical University 4Odessa National Medical University Summary Aim: To determine the preventive effect of the new antidysbiotic drug "Quertulidon" exercising the anti-helicobacter pyroli therapy (AHBT). Materials and methods: Rats have received AHBT (omeprazole in a dose of 1.3 mg / kg, amoxil in a dose of 50 mg / kg and clarithromycin in a dose of 7.5 mg / kg) per os for 8 days. The core group have been receiving oral administrations of phytogel "Quertulidon" (containing imudon, inulin, quercetin and calcium citrate) for 11 days extra. On the day 12, after euthanasia, blood, serum and tissue homogenates (liver, gums, mucous membranes of stomach and cheeks) were analyzed. In blood there were determined neutrophils, lymphocytes and lymphocytic index (LI — the ratio of lymphocytes to neutrophils). In serum and tissue homogenates there were determined inflammation markers (MDA and elastase), the rate of microbial contamination (by urease), the indicator of non-specific immunity (lysozyme) and the degree of dysbiosis by Levitsky. Results: AHBT induced the 3-fold increase in LI due to the decrease in the number of neutrophils. AHBT also induced the increase in the MDA, elastase and urease levels; it did the decrease in the lysozyme activity and large raise (2.5 — 5 times) of the degree of dysbiosis. Oral application of quertulidon normalized the level of lysozyme, reduced LI, significantly reduced the MDA, elastase and urease levels; and reduced the degree of dysbiosis by 1.4 — 1.8 times. Conclusion: Quertulidon has immunostimulant, antidysbiotic and anti-inflammatory effect that allows to suggest it for the prevention of AHBT-related complications. Keywords: Anti-helicobacter pylori therapy, immune deficiency, dysbiosis, inflammation, quertulidon. Резюме Антихеликобактерная терапия (омепразол, амоксил, кларитромицин) вызывает развитие неспецифического иммунодефицита, дисбиоза и воспаления. Оральные аппликации квертулидона (имудон, инулин, кверцетин и цитрат кальция) оказывают антидисбиотическое и противовоспалительное действие. Ключевые слова: антихеликобактерная терапия, иммунодефицит, дисбиоз, воспаление, квертулидон. Резюме РОЗВИТОК ДИСБІОЗУ І ЗАПАЛЕННЯ В ОРГАНІЗМІ ЩУРІВ, ЯКІ ОТРИМУВАЛИ АНТИХЕЛІКОБАКТЕРНУ ТЕРАПІЮ ТА ЇХ ПРОФІЛАКТИКА АНТИДИСБІОТИЧНИМ ПРЕПАРАТОМ «КВЕРТУЛІДОН». Антихелікобактерна терапія (омепразол, амоксил, кларітроміцин) викликає розвиток неспецифічного імунодефіциту, дисбіозу та запалення. Оральні аплікації квертулідону (імудон, інулін, кверцетин, цитрат кальцію) здійснюють антидисбіотичну та протизапальну дію. Ключові слова: антихелікобактерна терапія, імунодефіцит, дисбіоз, запалення, квертулідон.